2023
DOI: 10.58414/scientifictemper.2023.14.2.36
|View full text |Cite
|
Sign up to set email alerts
|

Yield and economics of bean (Phaseolus vulgaris L.) as affected by blended NPS fertilizer rates and inter row spacing at maenitgoldia, Southwest Ethiopia

Abstract: The common bean is one of Ethiopia's most economically important legumes. However, its national average yield remains lower than the potential yield obtained at research stations. This is because of low soil fertility, inappropriate plant spacing, disease and insect pest problems. As a result, this experiment was carried out during the 2021 to investigate the impact of blended NPS fertilizer rates and spacing between crops on the growth and yield of common bean and to analyze the economic feasibility of blende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…Te study suggests that blended NPSB rates led to increased biomass yield due to enhanced N availability, plant height, pod number, and vegetative growth. Tis fnding aligns with previous studies by Zewide et al [46], Mekonnen and Saliha [47], and Dela et al [48], which reported maximum biomass yields with varying NPSB fertilizer rates.…”
Section: Biomass Yieldsupporting
confidence: 90%
See 2 more Smart Citations
“…Te study suggests that blended NPSB rates led to increased biomass yield due to enhanced N availability, plant height, pod number, and vegetative growth. Tis fnding aligns with previous studies by Zewide et al [46], Mekonnen and Saliha [47], and Dela et al [48], which reported maximum biomass yields with varying NPSB fertilizer rates.…”
Section: Biomass Yieldsupporting
confidence: 90%
“…On the other hand, the decrease in grain yield associated with NPSB fertilizer rates beyond 125 kg•ha −1 may be attributed to an increased nitrogen rate, which promotes excessive vegetative growth in crop plants, consequently reducing the grain yield of common beans. Tis fnding aligns with previous studies by Arega and Mekonnen [42], Deresa [43], Tirfessa et al [45], Zewide et al [46], and Dela et al [48], which suggested that the increase in grain yield with the application of blended inorganic fertilizer could be attributed to the sufcient supply of N, P, S, and B soil solutions for crop uptake. Tis leads to an increase in the number of branches per plant and, subsequently, an increased photosynthetic area, resulting in more pods per plant and a higher number of seeds per pod.…”
Section: Grain Yieldsupporting
confidence: 90%
See 1 more Smart Citation